PENEGAKAN HUKUM LINGKUNGAN DI INDONESIA DALAM PERSPEKTIF UNDANG-UNDANG NOMOR 32 TAHUN 2009 TENTANG PERLINDUNGAN DAN PENGELOLAAN LINGKUNGAN HIDUP - W.WP.M.S, I.G.N. Wira; Dharma Saputra, Komang Edy (Jurnal Ilmiah Raad Kertha, 2024)
The Constitution of the Republic of Indonesia mandates the right to a good and healthy living environment. However, in practice, with the large number of environmental cases still occurring today, this can of course be a criticism of the Government as the organ that is fully responsible for fulfilling these rights. The various environmental problems that occur, both damage and pollution, are not directly proportional to the law enforcement mechanisms implemented by the Government. The birth of Law no. 32/2009 (PPLH Law) apparently has not been able to answer all the problems of environmental law enforcement in Indonesia. Law Number 32 of 2009 concerning Environmental Protection and Management (UUPPLH) has included criminal provisions in Chapter XV, which consists of 23 articles. These criminal provisions are much more complete and detailed when compared to the old Law Number 23 of 1997 concerning the Environment, but there are still many things that need to be addressed in the UUPPLH, therefore in this article we will describe the existing environmental law enforcement mechanisms. applies in Indonesia.